Teaching practices of excellent biology teacher - Balsicas, Nilda Wines (2005)
Selected biology teacher awardees' teaching practices were analyzed considering also their personal and professional characteristics, educational philosophy, self-perception and teaching style in constructing and implementing their instructional plan (IP). They all possess humility, respect for students and role modeling. They used eclectic philosophy in their teaching-learning transactions and has the tendency to use his/her distinct views on educational philosophy. They also hold distinct views on self-perceptions and beliefs on incoming students' entry level skills and concepts; knowledge, attitudes and skills to be learned; instructional methods and strategies; and student assessment strategies. The effective implementation of their IP is facilitated by their proficient use of the language of instruction.